RUPIAH EXCHANGE RATE FLUCTUATION AND CURRENT ACCOUNT - Santosa, Agus Budi; Nusantara, Agung; Nawatmi, Sri (Proceeding Fakultas Ekonomi, 2017)
The Rupiah exchange rate is an economic variable which is very sensitive toward the changes in both economy and non-economy. The stability of Rupiah exchange rate has influenced macro economic variables like current account and finally influenced economic stabilities. Thus, it is interesting to make a research on it. The research would choose and analyze approach models of Rupiah exchange rate to USA dollar connected with current account.The Ordinary Least Square analysis model was used in this test in order to find the relation between independent variable and dependent variable. The result of the study showed that exchange rate variable influence significantly to current account.This conclusion was in accordance to elasticity approach with Marshall-Lerner condition. Another result showed that gross domestic product influenced current account significantly and this was also in accordance to Global Monetary Approach Balance of Payment with purchasing power parity concept. Keywords : exchange rate, current account, economic stability, Marshall-Lerner condition, purchasing power parity.